A direct high step-down DC/DC converter using cascade ring-type converters - Kei Eguchi; Akira Shibata; Yujiro Harada (Energy Reports, 2020)
For data center applications, we present a direct high step-down DC/DC converter designed by using switched capacitor (SC) techniques. To achieve high step-down conversion, the proposed converter connects a novel cascade ring-type converter to a traditional buck converter. Unlike existing high step-down SC DC/DC converters, such as ladder-type SC converter, the proposed cascade ring-type converter provides (1/4)2 stepped-down voltage by using four-phase clock pulses, where a 48 V input is converted to 3V. In the buck converter, the output of the cascade ring-type converter is converted to 3D V (0<D<1). Hence, the proposed converter can achieve the (D/16) voltage gain by converting the 48 V input twice. Furthermore, small size and light weight are offered by the proposed converter with a single inductor. The performance of the proposed converter is evaluated by theoretical analysis, computer simulations, and bread board experiments. The evaluation results demonstrate that the proposed converter outperforms the conventional ladder-type SC converter in the point of power efficiency and output voltage.
Keywords: 330; Cascade connections; Data center applications; DC/DC converters; Ring-type converters; Step-down converters